2019
DOI: 10.1103/physrevx.9.021051
|View full text |Cite|
|
Sign up to set email alerts
|

Self-Trapping of Light Using the Pancharatnam-Berry Phase

Abstract: Since its introduction by Berry in 1984, the geometric phase has become of fundamental importance in physics, with applications ranging from solid-state physics to optics. In optics, the Pancharatnam-Berry phase allows the tailoring of optical beams by a local control of their polarization. Here, we discuss light propagation in the presence of an intensity-dependent local modulation of the Pancharatnam-Berry phase. The corresponding self-modulation of the wave front counteracts the natural spreading due to dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…Finally, the rotation angle will be bell‐shaped on the transverse plane xy, given that the local optical torque depends on the point‐wise value of the field intensity. This qualitative explanation is confirmed by numerical simulations as shown in reference [206]. After it is established that a CP beam is capable to induce a periodic rotation of the optical axis, the results from the linear case can be applied.…”
Section: Geometric Phase In Bulk Structuressupporting
confidence: 61%
See 3 more Smart Citations
“…Finally, the rotation angle will be bell‐shaped on the transverse plane xy, given that the local optical torque depends on the point‐wise value of the field intensity. This qualitative explanation is confirmed by numerical simulations as shown in reference [206]. After it is established that a CP beam is capable to induce a periodic rotation of the optical axis, the results from the linear case can be applied.…”
Section: Geometric Phase In Bulk Structuressupporting
confidence: 61%
“…Existence of this exotic type of waveguiding in a continuous (along z) structure has been recently provided. [ 206 ] Counter‐intuitively, the easiest way to write these guides is in the nonlinear regime, that is, where the perturbation in the material is induced by light itself via a nonlinear optical effect. To demonstrate this effect, reorientational nonlinearity in NLCs has been employed.…”
Section: Geometric Phase In Bulk Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, our proposed PhC consists of a single anisotropic dielectric material, but the band peculiarity comes entirely from the nontrivial periodic rotation of the optical axes inside the material. Although recent studies have shown that artificial gauge fields 47 , 48 , Pancharatnam-Berry phases 49 , and synthetic spin-orbit interactions 50 for light can be achieved by arranging the dielectric polarization, there are still few works that study the photonic band topology of PhCs made of anisotropic dielectrics. Our results suggest that the intrinsic material anisotropy has irreplaceable features compared to the structural anisotropy, and anisotropic dielectrics, such as liquid crystals 49 , 50 , could become a platform for probing the unique topological effects of EM fields.…”
Section: Discussionmentioning
confidence: 99%